2015
DOI: 10.1371/journal.pone.0140618
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Soluble CD26/Dipeptidyl Peptidase-IV in Type 2 Diabetes Mellitus and Its Association with Metabolic Syndrome and Therapy with Antidiabetic Agents in Malaysian Subjects

Abstract: BackgroundA soluble form of CD26/dipeptidyl peptidase-IV (sCD26/DPP-IV) induces DPP-IV enzymatic activity that degrades incretin. We investigated fasting serum levels of sCD26/DPP-IV and active glucagon-like peptide-1 (GLP-1) in Malaysian patients with type 2 diabetes mellitus (T2DM) with and without metabolic syndrome (MetS), as well as the associations between sCD26/DPP-IV levels, MetS, and antidiabetic therapy.MethodsWe assessed sCD26/DPP-IV levels, active GLP-1 levels, body mass index (BMI), glucose, insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
0
24
1
1
Order By: Relevance
“…To determine whether neprilysin directly inhibits DPP-4 activity, recombinant neprilysin was treated with the inhibitor dl -thiorphan and then incubated with recombinant DPP-4 in vitro at a neprilysin:DPP-4 molar ratio of 1:5 or 1:10, to match proportions found in plasma from lean and obese humans [3, 16, 17]. Measurement of DPP-4 activity showed that dl -thiorphan treatment resulted in 75±2% ( n =3, p <0.05) and 84±4% ( n =3, p <0.05) inhibition of neprilysin activity in samples containing neprilysin:DPP-4 molar ratios of 1:5 and 1:10, respectively, but had no effect on DPP-4 activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether neprilysin directly inhibits DPP-4 activity, recombinant neprilysin was treated with the inhibitor dl -thiorphan and then incubated with recombinant DPP-4 in vitro at a neprilysin:DPP-4 molar ratio of 1:5 or 1:10, to match proportions found in plasma from lean and obese humans [3, 16, 17]. Measurement of DPP-4 activity showed that dl -thiorphan treatment resulted in 75±2% ( n =3, p <0.05) and 84±4% ( n =3, p <0.05) inhibition of neprilysin activity in samples containing neprilysin:DPP-4 molar ratios of 1:5 and 1:10, respectively, but had no effect on DPP-4 activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant human DPP-4 (R&D Systems, Minneapolis, MN, USA) was then added at a final concentration of 0.01, 0.05 or 0.1 µmol/l, and incubated for 1 h at 37°C. When 1:1, 1:5 and 1:10 molar ratios of neprilysin to DPP-4 were tested, the 1:5 and 1:10 ratios approximated those documented in plasma from lean and obese humans [3, 16, 17]. Samples were assayed for neprilysin and DPP-4 activities as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The active principles of some plants, such as phytochemicals, inhibit DPP-IV enzyme activity [29]. Based on some findings, it is believed that DPP-IV level increased in diabetic condition and associated with long-term exposure to high levels of glucose [30]. The significant reduction in the incretin effect has been known to decrease the circulation level of GLP-1, which may be due to an increase in degradation by DPP-IV that leads to a decline in the mass and size of β-cell in the pancreas [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the demonstration that selective inhibition of DPP-4 enzymatic activity leads to robust induction of circulating sDPP4 without concomitant changes in inflammation raises further questions about the experimental and pathophysiological context linking changes in levels of sDPP4 to pro-inflammatory pathways. Intriguingly, DPP-4 inhibitors are widely used in conjunction with metformin, an agent associated with (1) reduced levels of circulating sDPP4 (Ahmed et al, 2015;Zhong et al, 2015) and (2) decreased numbers of major cardiovascular events, relative to DPP-4 inhibitors alone, in cardiovascular outcome studies (Crowley et al, 2017). Given the widespread use of DPP-4 inhibitors in human subjects with diabetes and inflammatory co-morbidities, including cardiovascular disease (Mulvihill and Drucker, 2014), it seems prudent to further elucidate the circumstances and co-factors linking changes in soluble and tissue DPP-4 with ambient DPP-4 activity, and sDPP4-mediated regulation of inflammation.…”
Section: Clinical Reports Associating Increased Plasma Levels Of Dpp-mentioning
confidence: 99%